Peruvian multiculturalism as an advertising tool - Perea-Ochoa, Jorge (2024)
The diversity of races, the lack of empathy with people outside an established social circle and racism are recurrent problems in Peruvian society. The turn of the century, the increase in the purchasing power of these ethnic groups and the emergence of multicultural markets brought a change of dynamics in the advertising industry. This study analyzes the multicultural attitudes present in the campaign #Celebrate our differences of the brand Inca Kola. Its approach is qualitative. Eighteen students of the last cycle of the anthropology career were interviewed. As a result, the spot fulfills its function of transmitting a message of unity between cultures thanks to the right ethnic signals. Multiculturalism, when used as a tool, brings benefits to the brand as it facilitates empathizing with the viewer, who is socio-culturally reflected in the product he/she consumes.